2021
DOI: 10.1103/physrevmaterials.5.034414
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-mediated control over the soft mode and ferroelectricity in BaTiO3

Abstract: We calculate the effects of conduction band electrons (CBEs), introduced by doping or photoexcitation, on the ferroelectricity and phonon dynamics of BaTiO3 (BTO). We show that CBEs destabilize ferroelectricity, which would lower the Curie temperature and coercive field, and might help to improve the speed or efficiency with which polarization domains can be switched in ferroelectric devices. We show that CBEs lower the frequencies of the A1 soft/ferroelectric modes in BTO's ferroelectric phases, and raise the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…18 The specific effects of doping on chemical bonding and the effect of electron-doping on ferroelectricity and phonon dynamics of BaTiO 3 were discussed by Hickox-Young et al and Gu et al, respectively. 19,20 In 2016, Benedek et al compared the effect of doping in LiOsO 3 and ATiO 3 perovskites (A = Ba, Sr, Ca). 6 They showed that the ferroelectricity is suppressed by electron doping in BaTiO 3 , whereas the non-centrosymmetricity in metallic LiOsO 3 and pseudocubic CaTiO 3 (with octahedral rotations not allowed) is robust to addition of charge carriers because of the local-bonding nature of the mechanism underlying the off-centering of the ions.…”
Section: Introductionmentioning
confidence: 99%
“…18 The specific effects of doping on chemical bonding and the effect of electron-doping on ferroelectricity and phonon dynamics of BaTiO 3 were discussed by Hickox-Young et al and Gu et al, respectively. 19,20 In 2016, Benedek et al compared the effect of doping in LiOsO 3 and ATiO 3 perovskites (A = Ba, Sr, Ca). 6 They showed that the ferroelectricity is suppressed by electron doping in BaTiO 3 , whereas the non-centrosymmetricity in metallic LiOsO 3 and pseudocubic CaTiO 3 (with octahedral rotations not allowed) is robust to addition of charge carriers because of the local-bonding nature of the mechanism underlying the off-centering of the ions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it would lower the energy cost of quantum fluctuation and therefore further enhance it (as if t/J is effectively increased) and consequently the polaron formation. Nonetheless, given the high energy barrier between the local dipolar modes (~105 meV for BaTiO 3 46,64 ), it is convenient to also drop the much weaker local fluctuation H R , considering that the corresponding fluctuation rate R must be orders of magnitude smaller than the eV energy scale of t and J. In other words, the time scale for such intrinsic fluctuation between dipolar modes is so long that it cannot possibly affect the much faster quantum polaron formation in any meaningful way.…”
Section: Physical Assumptions Of Numerical Approachesmentioning
confidence: 99%
“…While the introduction of H MD 36 and long-range H DD can slightly modify the internal shape of the polarons, it would not affect the qualitative trend since their energy is much smaller than that of the cooperative ligand displacement 52 . Similarly, given the already strong quantum fluctuation due to the eV-scale kinetic energy, it is convenient to also drop the much weaker local fluctuation H R , considering the small ∼20meV potential barriers between the local dipole modes in real materials 53 .…”
Section: Methodsmentioning
confidence: 99%